Dretske e o problema dos qualia - de Moraes, João Antonio; Gonzalez, Maria Eunice Quilici [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this paper is to present and discuss Fred Dretske's (1995) suggestion for analysis of the problem of qualia. Such a problem was acknowledged following Thomas Nagel's discussion in his classical paper What is it like to be a bat. In the paper, Nagel (1974) postulates the impossibility of knowing aspects of human experience from a third-person perspective. He considers that qualitative aspects of a subject's experience, fundamental for characterization of qualia, would be lost during the course of objective descriptions of it. Based on his Representational Thesis of Mind, Dretske argues that if we were to consider mind to be the representational aspect of the brain, the nature of qualia would thus be representational. In this context, mental facts related to experiences would be representational facts: if we were to know the nature of these representational facts, we would also know the experience the system represents. Given this understanding, we discuss to what extent the Dretskean proposal constitutes (or not) an alternative for the problem of qualia.
Dretske and the problem of qualia
Keywords: Displaced perception; Experience; Information; Qualia; Representation